Preparation and elevated temperature wear behavior of Ni doped WC-Al2O3 composite. (June 2019) - Su, Qingde; Zhu, Shigen; Bai, Yunfeng; Ding, Hao; Di, Ping
Abstract: With the more serious service environment, the new WC-Al2 O3 as coatings are required to apply in high-temperature wear condition. Owing to the severe deterioration of WC-Al2 O3 material in >500 °C, WC-Al2 O3 composites with different content of Ni were prepared using vacuum hot-pressing sintering technology with the aim of improving its elevated temperature wear behavior. Wear experiments of WC-Al2 O3 -x%Ni against YG6 ball (WC-6Co) were conducted at 600 °C using a commercially made high-temperature ball-on-disk tribometer. The mechanical properties and oxidation wear behavior of Ni doped WC-Al2 O3 composites were investigated. The phase and morphology of the sample surfaces were analyzed by XRD, EDS and SEM. The results show that the addition of Ni inhibited the decarburization of WC and ensured high mechanical properties. At elevated temperature, wear loss increased with loading. Without load, the mass loss decreased with the increase of Ni content. The minimum loss of WC-Al2 O3 composite with 10%Ni is 3.1 mg, decreased by 72.7%. When the load increased to 15 N, the mass loss of WC-Al2 O3 composite with 5%Ni is the minimum of 54.8 mg, decreased by 38.2%. On the whole, the addition of Ni is conducive to improving the resistance to oxidation wear. The wear mechanisms were dominated by oxidation wear and spalling of the tribolayer. Highlights: The addition of Ni reduced the sintering temperature of WC-Al2 O3 composite. Anti-oxidation wear behavior of Ni doped WC-Al2 O3 composite was improved. The wear loss were greatly dependent on elevated temperature and applied loads.